2014
DOI: 10.1063/1.4905022
|View full text |Cite
|
Sign up to set email alerts
|

Performance predictions of a focused ion beam from a laser cooled and compressed atomic beam

Abstract: Focused ion beams are indispensable tools in the semiconductor industry because of their ability to image and modify structures at the nanometer length scale. Here we report on performance predictions of a new type of focused ion beam based on photo-ionization of a laser cooled and compressed atomic beam. Particle tracing simulations are performed to investigate the effects of disorder-induced heating after ionization in a large electric field. They lead to a constraint on this electric field strength which is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…Particle tracing simulations that were performed earlier [13] showed that a reduction of the ion beam brightness due to disorder-induced heating can be prevented by applying an extraction electric field with such a magnitude that a so-called pencil beam is created. The extraction field needed to reach the pencil beam regime increases with the beam current since a larger beam current is made by increasing the size of the selection aperture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle tracing simulations that were performed earlier [13] showed that a reduction of the ion beam brightness due to disorder-induced heating can be prevented by applying an extraction electric field with such a magnitude that a so-called pencil beam is created. The extraction field needed to reach the pencil beam regime increases with the beam current since a larger beam current is made by increasing the size of the selection aperture.…”
Section: Methodsmentioning
confidence: 99%
“…After selection of the desired atomic flux, this beam is photoionized in the crossover of a tightly focused excitation laser beam and an ionization laser beam whose intensity is enhanced in a build-up cavity [12]. The ions are immediately extracted by an electric field in order to prevent disorder-induced heating which can lower the ion beam brightness [13]. The energy spread in the beam mostly originates from the distribution in the ionization position within this extraction field.…”
Section: Introductionmentioning
confidence: 99%
“…This source will be used to load the magneto optical compressor of the atomic beam laser cooled ion source 1,9 . The flux, transverse velocity spread and the brightness were measured using laser-induced fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…23). Kime et al, 14 Wouters et al 166 and ten Haaf et al 167 discuss an arrangement where an effusive atomic beam is first transversely cooled and then compressed using a two-dimensional MOT to create a very high flux atomic beam for ionization. The use of a 2D MOT has in fact been in the literature for some time as a way to make a bright neutral atomic beam, 168 and has been shown to be quite effective at compressing and transversely cooling a beam using the same velocity- and spatial-dependent forces present in a MOT, configured to act in two dimensions only.…”
Section: Cold Atomic Beam Sourcesmentioning
confidence: 99%
“…( 14, 166 and 167 ) are still under development, although very recently, imaging with a focused Cs + beam has been demonstrated with this type of source. 169 In an alternate approach, Knuffman et al 170 have constructed and demonstrated a cold atom beam ion source of Cs ions based on a somewhat different concept, with the goal of creating a high brightness source of heavy ions for milling and circuit edit applications (Fig.…”
Section: Cold Atomic Beam Sourcesmentioning
confidence: 99%